Peran Influencer dan Komunitas Digital dalam Mendorong Adopsi Produk - Kholifatur Rosyidah; Zahra Adinda Yahya; M. Ashiful Ardan; Achmad Chakim; Muhafidhah Novie (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This article discusses how product adoption in digital ecosystems is shaped by influencers and digital communities across several country contexts. The study applies a literature review with a qualitative synthesis approach using scholarly articles published between 2016 and 2026. The main goal is to compare key social mechanisms that repeatedly appear in adoption processes, especially trust, social proof, influencer credibility, message value, and reinforcement through live streaming. The synthesis shows that trust is the central node linking content exposure to purchase intention. In Western European contexts such as Belgium and the United Kingdom, consumers tend to rely on influencer signals like product fit, profile credibility, and popularity indicators. In France, parasocial interaction further strengthens the effect of credibility on purchase intention. In Indonesia, the combined role of influencers, communities, and live streaming can build trust quickly, yet it may also accelerate brand switching when trends shift. In Nordic contexts such as Sweden and Finland, and in cross country SME discussions, internal digital readiness and service consistency are crucial so adoption continues into stable customer experience and repeat purchase.